2000
DOI: 10.1088/0951-7715/13/2/305
|View full text |Cite
|
Sign up to set email alerts
|

Dipoles and similarity solutions of the thin film equation in the half-line

Abstract: We consider non-negative solutions on the half-line of the thin film equation h t + (h n h xxx) x = 0, which arises in lubrication models for thin viscous films, spreading droplets and Hele-Shaw cells. We present a discussion of the boundary conditions at x = 0 on the basis of formal and modelling arguments when x = 0 is an edge over which fluid can drain. We apply this discussion to define some similarity solutions of the first and the second kind. Depending on the boundary conditions, we introduce mass-prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 41 publications
(92 reference statements)
2
60
0
Order By: Relevance
“…Bernis, Hulshof and King [5] consider u t = −(u n u xxx ) x on the half-line [0, ∞). At x = 0 they consider two types of boundary conditions: no-flux and zero contact angle.…”
Section: 2mentioning
confidence: 99%
“…Bernis, Hulshof and King [5] consider u t = −(u n u xxx ) x on the half-line [0, ∞). At x = 0 they consider two types of boundary conditions: no-flux and zero contact angle.…”
Section: 2mentioning
confidence: 99%
“…Recent years, there are also many researches devoted to symmetry group structure and exact solutions of the fourth-order thin film equations (1) and their generalizations [16][17][18][19][20][21][22][23][24][25], or searching for special invariant finite vector spaces of solutions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Formal analysis of the asymptotic behaviour of solutions near the boundary [3,9,10] suggests that for n > 2 the flux h n h xxx at the boundary is always inwards and has to be prescribed. This does not make much sense in the context of draining and it clearly falls outside the scope of (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…For n < 2 it is found that outward flux is a genuine possibility. Although (for n < 3 2 ) the support may initially retract from the fixed boundary, it eventually covers the whole interval and draining occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation